Visual and ocular motor function in the atypical form of neurodegeneration with brain iron accumulation type I - Jesus-Ribeiro, J (2018)
BACKGROUND/AIMS: Neurodegeneration with brain iron accumulation (NBIA) type I is a rare disease that can be divided into a classical or atypical variant, according to age of onset and clinical pattern. Neuro-ophthalmological involvement has been documented in the classical variant but only anecdotically in the atypical variant. We sought to describe the visual and ocular motor function in patients with atypical form of NBIA type I. METHODS: Cross-sectional study, including patients with genetically confirmed NBIA type I and classified as atypical variant, who underwent ophthalmological examination with best corrected visual acuity (BCVA), optical coherence tomography (OCT), fundus autofluorescence (FAF), electroretinography (ERG), visual evoked potentials (VEP) and video-oculography. RESULTS: Seven patients with a mean BCVA of 0.12±0.14 logMAR were included. Only two patients showed structural evidence of advanced retinopathy in OCT and FAF, and there were no cases of optic atrophy. ERG data, however, showed abnormal scotopic and/or photopic responses in all patients. VEP were normal in all three patients. Ocular fixation was markedly unstable (eg, increased rate of saccadic pulses) in the majority of patients (5). Additional mild ocular motor disturbances included low gain pursuit (2), hypermetric saccades (1), low gain optokinetic (2) and caloric and rotatory responses (3). CONCLUSION: Functional retinal changes associated with marked instability of ocular fixation should be included in the clinical spectrum of NBIA, particularly in the atypical form.